THE ‘USUS’ AS A WAY TO PUT A WOMAN UNDER THE AUTHORITY OF HER HUSBAND - Chmielecka, Magdalena (Zeszyty Prawnicze, 2019)
The article addresses issues relating to the institution of usus, which was one of the ways a woman could be put under her husband’s authority and power. One of the points discussed is the origin of this institution. I consider the signifcance of the location of usus in the source documents. The fundamental question in research on usus is the determination of the date on which a period of usus started, in other words usus was treated as a sort of usucaption, which implied a date on which it would finish. I also discuss issues connected with usurpatio trinoctii.